ANALISIS KEBUTUHAN AWAL PENGEMBANGAN MEDIA PEMBELAJARAN ARTICULATE STORYLINE PADA PEMBELAJARAN MEMBACA DI SEKOLAH DASAR - Manuain, Yemima; Nurul Istiq’faroh; Wahyu Sukartiningsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Education is a very important aspect and must be obtained by every individual. In learning, appropriate media and strategies are needed to support the process. For elementary school students, reading is an important skill for students to master to support their learning activities. This research aims to analyze the need for appropriate learning media in improving students' reading comprehension skills in elementary school. Data collection was carried out using interview and observation methods with teachers and grade 4 students at SDN Lidah Wetan IV Surabaya. From the results of interviews and observations, it was found that teachers are still unable to create more varied learning media to use in learning, due to a lack of knowledge and skills to create learning media and it takes quite a long time. The learning strategy used is still conventional, one-way and not interactive. Students' reading comprehension skills are still relatively low. Students are still unable to determine explicit information in reading texts, understand unfamiliar words or terms, and cannot focus when participating in reading activities in class. Based on the results of the research that has been carried out, it can be concluded as follows: 1) The use of media and strategies used by teachers in learning is still conventional and not interactive, 2) Students' reading comprehension skills are still relatively low, and 3) Teachers need learning media for articulating story lines to improve students' reading comprehension skills.